Correlation between the crystallization process and change in electron density of states in amorphous powder of the Ni80Co20 alloy - Ranđić S.; Maričić A.; Rafailović L.; Spasojević M.; Ristić M.M. (Science of Sintering, 2006)
The method of differential scanning calorimetry (DSC) was employed to examine the crystallization process of amorphous powder of the Ni80Co20 alloy in the temperature interval from room temperature to 1000K. It is shown that the crystallization process of this alloy's powder proceeds in two stages at temperatures T1=690K and T2=790K. The relative changes in the electron density of states in the vicinity of Fermi level were determined from the changes in the slope of the thermo-electromotive force (TEMF) temperature coefficient before and after each stage of crystallization process. The obtained results show that the relative change in the electron density of states is 34.9% after the first crystallization stage and 38.9% after the second one. The changes in the specific electrical resistance of the pressed powder as a function of temperature are fully correlated with the change in the electron density of states and results of the DSC method. The observed rapid decrease in the specific electrical resistance after each crystallization stage is caused by the increase of the mean free electron path and increase in the electron density of states.